Decision Support System for Selecting Student Recipients of Single Tuition Fee (STF) Assistance using Multi-Objective Optimization on the Basis of Simple Ratio Analysis (MOOSRA) Method - Sihombing, Johannes Syahputra; Naibaho, Dahner Junedi; Mesran (International Journal of Informatics and Data Science, 2025)
Single Tuition Fee (STF) is a tuition fee borne by each prospective new student based on their economic capability. The process of determining the STF groups requires precision and time, as student data needs to be compared with the STF criteria one by one. The decision-making system in determining the STF groups that exist currently utilizes five criteria in assessing the parents' ability to pay for their child's education, namely: Parental Income, Possession of PKH Card, Document Completeness, Parental Dependents, and Academic Performance. Therefore, a decision support system is needed that applies the MOOSRA method to assist in determining the STF groups. There are five criteria used in this research: parental income, ownership of the PKH card, document completeness, parental dependents, and academic performance. The calculation results for several sample data yield the best final optimization value in the selection of students eligible for STF assistance, which is found in alternative A7 (Meli) with a total score of 0.863.